The Growth Enhancement in Three Arabica Coffee Clones by Frequent Watering in Seedling Stage - Ismaya, Doni Febri; Ikhwan, Ali; Indratmi, Dian; Pranata Erdiansyah, Novie (Indonesian Coffee and Cocoa Research Institute, 2023)
Coffee cultivation in Indonesia generally only relies on rainfall as a source of water. Drought that occurs in the dry season inhibits growth, reduces yields, and even death of plants. Not all plants are equally resistant to drought conditions. Drought-resistant coffee clones usually develop several resistance mechanisms, including the formation of specific compounds to protect cells and tissues from damage caused by drought stress. Therefore, the objective of this study was to investigate the influence of watering interval on the seedling growth of three clones of Arabica coffee. This study used applying intervals of watering every two, four and six days as first factor and three Arabica coffee clones as second factor, namely Andungsari 2K, S 795, and Andungsari 1. The experimental design used a factorial completely randomized design where every treatment combination had three replications. This study on Arabica coffee nursery lasted for three months. Results obtained in this study demonstrated that combination of watering every four and six days on Andungsari 2K clone had the best values on several observed variables. Number of stomata, leaf thickness, fresh root weight, and root dry weight were larger for watering every six days on the Andungsari 2K clone, meanwhile leaf number, stem diameter, fresh and dry weight of leaves were larger for watering every four days on Andungsari 2K clone. This study showed that there was an interaction between watering intervals and Arabica coffee clones on plant growth. Treatment combination of watering every six and four days on Andungsari 2K clone significantly affect number of stomata, fresh root weight, and root dry weight especially for watering every six days on Andungsari 2K clone.